(untitled) (Bangladesh Journal of Pharmacology, 2012)
The objective of the current study is to evaluate the phosphodiesterase inhibitory activity of flavonoids using in silico docking studies. In silico docking studies were carried out using AutoDock 4.2, based on the Lamarckian genetic algorithm principle. The results showed that all the selected flavonoids showed binding energy ranging between -7.50 kcal/mol to -6.61 kcal/mol when compared with that of the standard (-4.77 kcal/mol). Inhibition constant (3.17 µM to 14.36 µM) and intermolecular energy (-9.29 kcal/mol to -8.70 kcal/mol) of the ligands also coincide with the binding energy. All the selected flavonoids contributed better phosphodiesterase inhibitory activity because of its structural parameters. Benzopyran ring in the flavonoids are majorly contributed its activity. These molecular docking analyses could lead to the further development of potent phosphodiesterase inhibitors for the treatment of inflammatory diseases.